Tactics of Primary Emergency Radiation Diagnosis of Politrauma - Yu. G. Shapkin; P. A. Seliverstov; N. Yu. Stekolnikov (Вестник рентгенологии и радиологии)
The review considers the problem of choosing the optimal tactical approach to primary emergency radiation diagnosis of injuries during polytrauma based on data on indications for use, advantages and disadvantages of modern methods and protocols of radiation imaging. Literary sources were searched in the MedLine/ PubMed and eLibrary databases published from 2009 to 2019.The tactics of selective radiation diagnosis of polytrauma involves performing sequential studies (sonography, X-ray, computed tomography) of body areas in which damage is suspected by the mechanism of injury and clinical data, which limits the accuracy of the diagnosis and increases the duration of the examination. Primary multi-helical “whole-body”computed tomography including head, neck, chest, abdomen and pelvis examination, reduces the percentage of missed injuries, the duration of the examination and the time before emergency surgery, which can significantly reduce mortality in polytrauma. Its use is justified in patients with severe combined trauma if a high level of emergency hospital care organization is provided. Using “whole-body” computed tomography significantly increases the dose and economic costs, but the benefits of it for the survival of patients with polytrauma can outweigh the radiation risk and economic losses. Further development of technologies and protocols for multispiral computed tomography can significantly reduce the dose of radiation and the duration of the study. Clear and well-founded criteria for the selection of patients are needed for whom the use of “whole-body” computed tomography will be an effective strategy for radiation diagnosis.